2k=k-35

Simple and best practice solution for 2k=k-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k=k-35 equation:


Simplifying
2k = k + -35

Reorder the terms:
2k = -35 + k

Solving
2k = -35 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
2k + -1k = -35 + k + -1k

Combine like terms: 2k + -1k = 1k
1k = -35 + k + -1k

Combine like terms: k + -1k = 0
1k = -35 + 0
1k = -35

Divide each side by '1'.
k = -35

Simplifying
k = -35

See similar equations:

| 4x-3(x-5)=45 | | y/-5+4=13 | | X/-4=-4-(-6) | | s+6/2=12 | | 85+2x=90 | | 8x-5x=-12 | | 4x^2-24x+11=0 | | 2x^2-31x+42= | | 1/3(3-4t)=6 | | 11(2x+4)-1/5(12x+1/2x-170)=39(1/2x+2) | | -7a=-9-4a+3 | | 39y=19(2y+14) | | 4x+1=1x+8 | | t/-4=-3pi | | x+5y=6y | | 13=y/5+3 | | 2x^2-23x+56= | | 2z=12-18 | | 3-3=18x+10x | | 4=3.5x | | 1/5x3/7x10/7 | | X+3=sx-61 | | 3(7-5)+2=5 | | 2x+18+3x+5+2x+17=180 | | 6m-5=4m+5 | | -7=n+12 | | -7x-6+3x=-42 | | 14(-12-8x)=392 | | 19x-11-17+14=2x+3 | | n+6*n+6-7=99 | | 81-4x=7-9x | | v+4/v-4=5-v/v-2 |

Equations solver categories